Disinfection of Irrigation Water Using Titanium Electrodes. Issue 6 (21st June 2021) - Qing, Geletu; Abolhassani, Mojtaba; Daneshpour, Raheleh; Foster, Shelby L.; Matlock, Marty; Thoma, Greg; Greenlee, Lauren F.
Abstract : This work reports on the electrochemical disinfection of natural irrigation water collected from the Waiahole Ditch Irrigation System in Hawaii using a batch cell assembled with titanium electrodes as both anode and cathode. Disinfection experiments were performed by applying a polarity-reversing direct current between the two titanium electrodes. The naturally occurring concentration of chloride in the water was 1.84 mg l −1 and no other chemicals were added. The applied current density was varied between 0 mA cm −2 and 2 mA cm −2, and the half-period ( T /2) of the polarity-reversing direct current was varied between 5 s and 60 s. The best disinfection performance was achieved at 2 mA cm −2 and T /2 = 10 s, requiring only 5 min of treatment for the complete disinfection of E. coli (4-log reduction). E. coli was inactivated by free chlorine species electrogenerated at the titanium electrodes. Hydrogen peroxide, short-lived oxidants, and direct electron transfer most likely had minor contributions to the disinfection process. During the disinfection experiments, the concentrations of disinfection byproducts (ClO3 −, CHCl3, CHBrCl2, CHBr2 Cl, and CHBr3 ) were significantly lower than recommendations for drinking water. The titanium electrodes consumed less electrical energy than platinum-coated titanium electrodes because they needed a lower current density to achieve similar disinfection efficiency.